Effect of Moringa Leaves Ethanolic Extract (Moringa oleifera, Lam.) on Testicles Histopathological Structure in Metabolic Syndrome Rat Model - Aji, Febriagi Bayu; Setyawan, Novan Adi; Hakim, Fikar Arsyad; Pesik, Riza Novierta (Faculty of Medicine Universitas Sebelas Maret, 2023)
Introduction: Metabolic syndrome was a collection of various disorders that can significantly increase the risk of experiencing insulin resistance, atherosclerotic cardiovascular disease, vascular complications, and diabetes mellitus. The detrimental effect of this condition has led to the development of various treatments options, such as Moringa leaves extract (Moringa oleifera), which was suspected to have ameliorative effects. Therefore, this study aimed to determine the effect of Moringa leaves extract on the histopathological appearance of the testes of Wistar rats induced with metabolic syndrome.Methods: This was an experimental design study, with a post-test-only control group, involving 30 Wistar rats (Rattus norvegicus). Metabolic syndrome was induced in the samples through the administration of high-fat and fructose feeds along with streptozotocin and nicotinamide. Furthermore, the moringa leaves extract was administered to the treatment groups in different doses of 150, 250, and 350 mg/kg BW. Testicular histopathological damage scores were then assessed on each group. The Kruskal-Wallis test which followed by Mann-Whitney test was used to determine the significant differences between the groups, while the correlation was analyzed using Spearman test.Results: There were significant differences in the histopathological scores between the treatment and control groups. Furthermore, the Wistar rats treated with Moringa extract showed better histopathological scores (2.1±0.64) compared to those without the treatment (2.7±0.54), p<0.05. The results also showed that higher doses of the extract significantly correlated with better outcome in testicular histopathological structure of metabolic syndrome rat model (p=0.000, r=-0.396).Conclusion: Moringa leaves ethanolic extract treatment improved testicular histopathological appearance in Wistar rats induced with metabolic syndrome.